Insights into Lead Toxicity and Detoxification Mechanisms in the Silkworm, Bombyx mori - Dan-Dan Bian; Yan-Xia Shi; Kai-Wen Shi; Hui-Cong Du; Bo-Ping Tang; Qiu-Ning Liu (Insects, 2025)
Bombyx mori, a key lepidopteran model with economic importance, is highly susceptible to environmental heavy metal pollution. This study investigated the mechanisms of Pb toxicity and the associated detoxification and metabolic defense responses in silkworms, employing transcriptome sequencing, enzyme activity assays, and histopathological analysis. Pb exposure caused significant histopathological changes and apoptosis in the fat body, marked by structural disorganization, swollen adipocytes, and degraded extracellular matrix. Molecular analysis showed activation of antioxidant defenses, with superoxide dismutase (SOD) and catalase (CAT) activities significantly elevated (p < 0.05), while peroxidase (POD) activity declined (p < 0.05). Levels of malondialdehyde (MDA) and glutathione (GSH) also decreased. In detoxification responses, carboxylesterase (CarE) activity was reduced, whereas cytochrome P450 (P450) and glutathione S-transferase (GST) activities increased (p < 0.05). Transcriptome sequencing revealed 1,418 differentially expressed genes (DEGs), with notable upregulation of key detoxification genes (p < 0.05), including six cytochrome P450s (CYPs), five uridine diphosphate-glycosyltransferases (UGTs), three glutathione S-transferases (GSTs), and six ATP-binding cassette transporters (ABCs). KEGG enrichment analysis highlighted the involvement of these DEGs in drug metabolism, glutathione metabolism, and ABC transporter pathways (p < 0.05). Functional validation showed that knocking down Cap ‘n’ Collar C (CncC) significantly suppressed key detoxification genes (CYP18A1, CYP332A1, GSTd3, GSTt1, UGT33D8; p < 0.05). qRT-PCR and Western blot analyses confirmed that the Caspase-3 pathway mediates Pb-induced apoptosis, with increased cleaved Caspase-3 and Caspase-4 levels following CncC silencing. Overall, our findings elucidate the mechanisms of Pb toxicity in silkworms and identify CncC as a critical regulator of detoxification and defense against heavy metal stress in lepidopteran insects.